The therapeutic promise of ATP antagonism at P2X3 receptors in respiratory and urological disorders - Ford, Anthony; Undem, Brad (Frontiers in Cellular Neuroscience, 2013)
A sensory role for ATP was proposed long before general acceptance of its extracellular role. ATP activates and sensitizes signal transmission at multiple sites along the sensory axis, across multiple synapses. P2X and P2Y receptors mediate ATP modulation of sensory pathways and participate in dysregulation, where ATP action directly on primary afferent neurons (PANs), linking receptive field to CNS, has received much attention. Many PANs, especially C-fibers, are activated by ATP, via P2X3-containing trimers. P2X3 knock-out mice and knock-down in rats led to reduced nocifensive activity and visceral reflexes, suggesting that antagonism may offer benefit in sensory disorders. Recently, drug-like P2X3 antagonists, active in a many inflammatory and visceral pain models, have emerged. Significantly, these compounds have no overt CNS action and are inactive versus acute nociception. Selectively targeting ATP sensitization of PANs may lead to therapies that block inappropriate chronic signals at their source, decreasing drivers of peripheral and central wind-up, yet leaving defensive nociceptive and brain functions unperturbed. This article reviews this evidence, focusing on how ATP sensitization of PANs in visceral “hollow” organs primes them to chronic discomfort, irritation and pain (symptoms) as well as exacerbated autonomic reflexes (signs), and how the use of isolated organ-nerve preparations has revealed this mechanism. Urinary and airways systems share many features: dependence on continuous afferent traffic to brainstem centers to coordinate efferent autonomic outflow; loss of descending inhibitory influence in functional and sensory disorders; dependence on ATP in mediating sensory responses to diverse mechanical and chemical stimuli; a mechanistically overlapping array of existing medicines for pathological conditions. These similarities may also play out in terms of future treatment of signs and symptoms, in the potential for benefit of P2X3 antagonists.